Experimental investigation of sodium polyacrylate-based innovative adsorbent material for higher desalination and cooling effects. (15th August 2022) - Alsaman, Ahmed S.; Ibrahim, E.M.M.; Salem Ahmed, M.; Ali, Ehab S.; Farid, A.M.; Askalany, Ahmed A.
Highlights: Sodium polyacrylate (SP) is investigated as an adsorbent. Composite SP/CaCl2 has been presented. Characteristics of raw SP, SP/HCl, SP/(NH4 )2 CO3 ), and SP/CaCl2 have been studied. AD system has been modeled employing SP/CaCl2 . Fresh water production of 41 m 3 /ton has been recorded. Abstract: This study explores enhancing adsorption system's performance utilizing sodium polyacrylate (SP) as an adsorbent for the first time. Four innovated SP samples are explored: raw SP, SP/HCl, SP/(NH4 )2 CO3 ), and SP/CaCl2 composite for adsorption desalination and cooling applications. Different characterization methods, including X-ray diffraction, nitrogen adsorption isotherm, and water adsorption (isotherms and kinetics) of SP samples, are investigated. Water adsorption experimental results onto SP samples and their numerical fitting with the Dubinin-Astakhov equilibrium model for isotherms and linear driving force model for kinetics have been expressed. The composite SP/CaCl2 had the highest experimental adsorption uptake of 1.26 kgH2 O/kg among the studied samples. At 85 °C regeneration temperature, water desalination production per day (SDWP) achieves 15 m 3 /ton, with a cooling power of 425 W/kg. SDWP could reach 41 m 3 /ton of SP/CaCl2 per day with heat recovery. The system can obtain an SDWP of 45 m 3 /ton per day at a regeneration temperature of 95 °C. The findings show that the system can run efficiently using renewable energy, waste heat, or geothermal energy as heat sources.